Effects of Cooperative Learning vs. Traditional Instruction on Prospective Teachers’ Learning Experience and Achievement - Zaheer AHMAD; Nasir MAHMOOD (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi)
The study investigated the effects of three experimental conditions on prospective teachers’ learning experience and achievement in the course of Educational Psychology. The conditions comprised (a) Traditional Instruction (TI) (b) Cooperative Learning Loosely Structured (CLLS) and (c) Cooperative Learning Students Team Achievement Division (CL STAD) model. The study explored change in students’ scores on learning experience and difference in achievement under these experimental conditions. Thirty-two student teachers enrolled in master degree program were the subjects of the study. Repeated measure design was used for the study. Thirty intervention lessons (ten in each condition) were delivered during the whole semester. Learning experience measure and Achievement test were administered at the end of each phase. The results of repeated measure analyses of variance (ANOVA) reveal that there is statistically significant difference between prospective teachers’ scores on learning experience measure across three experimental conditions. ANOVA results also reveal that there is a statistically significant difference in achievement scores favoring both CL conditions. The study concludes that cooperative learning enhances perspective teachers’ academic achievement as compared to traditional instruction and promotes enriched, enjoyable and interactive learning experience. The study has implications for teacher educators to prefer innovative instructional strategies as CL while teaching to prospective teachers